Relationship of dietary energy and heat tolerance in sheep - Karim, S A; Patyanak, B C (The Indian Journal of Animal Sciences, 2012)
Relationship between dietary energy and heat tolerance of Mutton synthetic rams was assessed by feeding them on 100 % of their maintenance energy requirement under shed (G1) and solar exposure (G2) or 115 (G3) and 130 (G4)% of their energy requirement under summer sun. DMI was similar in all the groups as per experimental design whereas water consumption was higher in G3 compared to G1, G2 and G4. The rams exposed to heat had average water consumption of 11.5 % of body weight amounting to 6.23 I/kg DMI. The respiration frequency (RF) registered usual variation increasing by 210 % from morning to peak hot period (PHP) in these heat exposed rams. Such increase in RF was of lower magnitude in animals under protection compared to solar exposed groups and the trends remained same on its expression in terms of unit rise in rectal temperature (RT). The RF in the 2 recordings and its increase for unit °C rise in RT was higher (P<0.01) in G4 followed by G3, G2 and G1 in that order. Pulse rate (PR) increased by 24% from morning to PHP. PR was higher in G3 and G4 than in Gland 02 both in morning and PHP recordings, however, the increase in PR from morning to PHP was higher in G2 than other groups. The rectal temperature (RT) was 38.8 °C in morning and increased to 39.4 °C at PHP. Morning RT was higher in G4 (38.96 °C) arld G3 (38.80 °C) than G1(38.72 °C) and G2 (38.71°C). The increase in RT from morning to PHP was lower (P<0.01) in High energy fed G4 and higher in Gland G3 in that order whereas highest values were recorded in G2. Sweating rate at PHP was lower in G1 under shed (133 g/m²/hr) than solar exposed G2, G3 and G4 (227 g/m²/hr) and among the solar exposed groups it was lower in G4 and G2 than G3. It is concluded that although heat exposed, high energy feed groups exhibited greater respiratory distress, their morning to peak hot period increase in rectal temperature was of lower magitude indicating better heat tolerance.